2011 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2011
DOI: 10.1109/iembs.2011.6090465
|View full text |Cite
|
Sign up to set email alerts
|

Decoding of individuated finger movements using surface EMG and input optimization applying a genetic algorithm

Abstract: In this paper we present surface electromyo-graphic (EMG) data collected from 16 channels on five unimpaired subjects and one transradial amputee performing 12 individual finger movements and a rest class. EMG were processed using a traditional Time Domain feature-set and classifiers: a Linear Discriminant Analysis (LDA) a k-Nearest Neighbors (k-NN) and Support Vector Machine (SVM). Using continuous datasets we show that it is possible to achieve an accuracy up to 80% across subjects. Thereafter possibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
2
7
0
1
Order By: Relevance
“…In fact, as demonstrated by Farrell and Weir with an extensive work on pattern recognition 29 that compared different feature sets and recording techniques (targeted surface, targeted intramuscular, and untargeted surface electrodes), the fundamental requirement is the ability of the algorithm to accurately identify a pattern, regardless of which feature set or recording technique is used. Other studies 11,30 reached the same conclusions when dealing with individuated finger movements.…”
Section: Discussionsupporting
confidence: 73%
“…In fact, as demonstrated by Farrell and Weir with an extensive work on pattern recognition 29 that compared different feature sets and recording techniques (targeted surface, targeted intramuscular, and untargeted surface electrodes), the fundamental requirement is the ability of the algorithm to accurately identify a pattern, regardless of which feature set or recording technique is used. Other studies 11,30 reached the same conclusions when dealing with individuated finger movements.…”
Section: Discussionsupporting
confidence: 73%
“…Also, almost all of the current works only deals with small number of classes (less than 10) [11,[17][18][19][20]23,29,30]. Only an extremely small number of studies have reported classification results for more than 10 classes but they require large number of electrodes [21,[31][32][33]. However, this option may not be possible with an amputee.…”
Section: Related Workmentioning
confidence: 99%
“…At the same time, it is also inconvenient for healthy people to wear many electrodes. Works by Tenore et al [21] Kanitz et al [33] show that accurate classification of 12 finger motions is possible but they also face the disadvantage of having very large number of electrodes. In contrast, our work involves a smaller number of electrodes on the forearm which contributes to reducing equipment costs and preparation time, hence increases the usability of the system.…”
Section: Classification Of 17 Voluntary Movementsmentioning
confidence: 99%
“…Proportional EMG control [20] and pattern recognition based EMG control [21] of prosthetics are paradigms also used in orthotics. Prosthetic EMG control of individual finger motions [22], [23] and prosthetic EMG control which determines force and grasp type [24] have been explored. Control optimization studies have informed both signal processing [25], [26] and control hierarchy [27] of prostheses.…”
Section: Introductionmentioning
confidence: 99%